Implementasi Metode Nurul Bayan Pada Pembelajaran Tahsin Al-Qur’an - Utami, Nurul; Budianto; Subandrio (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
The aims of this study were 1) to find out the application of the nurul bayan method to learning Al-Qur'an tahsin in one of the Islamic elementary schools in Bekasi. 2) To determine the supporting and inhibiting factors of the nurul bayan method. The research method used is a qualitative research approach with descriptive qualitative methods. Data collection uses interviews, observation and documentation using data collection analysis, data reduction, data display and conclusion drawing/verification. The results of the study revealed that: 1) The application of the nurul bayan method to learning Al-Qur'an tahsin in one of the Islamic elementary schools in Bekasi begins with preparing material, before starting learning students pray first then students listen to Al- Qur'an recitation followed by the tajwid law contained in it, after that it is repeated several times, then students are grouped and appointed one by one to read the verses that have been read by the teacher, then continue with writing. 2) The supporting factors and inhibiting factors for the nurul bayan method are the supporting factors, namely the book used is very concise and easy to teach to students while the inhibiting factors are age, language and class management factors.